Posttraumatic growth in survivors of a natural disaster: the role of social axioms of religiosity, reward for application, and social cynicism. Issue 4 (4th July 2017) - Nalipay, Ma. Jenina N.; Bernardo, Allan B. I.; Mordeno, Imelu G.
Abstract: The positive psychology movement has impelled trauma research to focus not only on debilitating aspects of trauma experiences, but also on its positive outcomes such as posttraumatic growth (PTG). We investigated how the social themes of religiosity, reward for application, and social cynicism, as part of the individual's distal culture, contribute to PTG among natural disaster survivors. We tested a model wherein social axioms of religiosity, reward for application, and social cynicism predict PTG, and their relationships are mediated by adaptive cognitive processing of trauma. The model was tested in a sample of Filipino survivors of typhoon Haiyan using structural equation modeling. The results support the proposed model except for the influence of social cynicism. The findings suggest that generalized beliefs about the social world play an important role in the development of PTG, and must be considered to understand how growth occurs in the aftermath of a traumatic event.